Transport Distraction Osteogenesis for Maxillomandibular Reconstruction: Current Concepts and Applications - Neelakandan, R. S. (Springer-Verlag, 2011)
Reconstruction of the facial skeleton remains a herculean task for a reconstructive surgeon, even with the availability of ample reconstructive options. Transport distraction osteogenesis is a novel reconstructive modality in the armamentarium of a maxillofacial reconstructive surgeon with obvious advantages of osteogenesis and histogenesis from the residual host tissues after tumor ablative surgeries or trauma and also, precludes donor site morbidity. This paper reviews the current concepts, principles involved and applications of transport distraction osteogenesis in maxillomandibular reconstruction.